Learning from the West, learning from the East: the emergence of the study of Buddhism in Japan and Europe before 1900 - Licha, Stephan; Krämer, Hans Martin (Studies on East Asian religions, 2023)
"The essays collected in this volume for the first time foreground the fundamental role Asian actors played in the formation of scholarly knowledge on Buddhism and the emergence of Buddhist studies as an academic discipline in Europe and Asia during the second half of the nineteenth century. The contributions focus on different aspects of the interchange between Japanese Buddhists and their European interlocutors ranging from the halls of Oxford to the temples of Nara. They break the mould of previous scholarship and redress the imbalances inherent in Eurocentric accounts of the construction of Buddhism as an object of professorial interest. Contributors are: Micah Auerback, Mick Deneckere, Stephan Kigensan Licha, Hans Martin Krämer, Ōmi Toshihiro, Jakub Zamorski, Suzanne Marchand, Martin Baumann, Catherine Fhima, and Roland Lardinois"--
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Geschichte 1850-1900; Forschung; Buddhismus; Europa; Japan